Formulation of architectural design guidelines for technological universities in Myanmar - Shwe, Theingi (2008)

(untitled)
This research paper presents the guidelines of architectural design for technological university academic buildings, which is appropriate for Myanmar context. The objective of this research is upgrading technological university academic building design according to national technology, science and to suit education system. The scope of the research is confined to the study of the academic buildings space descriptions, the requirements and preliminary factors of designing new buildings or renovation existing buildings. The employed methodology of this applied research is consisted of greatly three main parts. The first portion is reviewed and study on educational background, theoretical description and space standards from literature. The second is field survey and practically analysis on existing technological universities and colleges of foreign and local as textual, visual and situation analysis. The result of this research is contributed by formulating guidelines in order to assist in the process of designing technological university academic buildings and preparation of accommodation schedule. In the formulation of general design guidelines, three optimum sizes of technological universities for Myanmar are assumed in order to determine as basic concepts for determining accommodation schedule. To suit these optimum sizes, the functional requirements, the space allocation, area requirements and accommodation schedule are formulated. Moreover, the architectural designs guidelines are proposed for functional relationship and desirable space composition of academic area in the design process.